Adaptive Expectation Stability Model in Controlling Inflation and Unemployment in Heaven Earth Countries - Fredi Alwi; Wahyu Indah Sari; Lia Nazliana Nasution (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Adaptive Expectation Stability Model in controlling Inflation and Unemployment in Heaven Earth Country, which functions to see the picture of Inflation and Unemployment conditions in the following year. This study aims to Analyze Gross Domestic Product, Interest Rates and Money Supply affecting Inflation and Unemployment in the short, medium and long term and Analyze the differences in Inflation and Unemployment before and during the Covid 19 pandemic in Heaven Earth Country. This type of research is quantitative analysis using secondary data in time series from 2006 to 2021 (time series) and cross-sections obtained from the World Bank and BPS. The data analysis techniques used are the VAR method and Difference Test. Analysis Results The results of the VAR analysis show that past variables (t-1, t-2) have contributed to the current variables, both for the variables themselves or for other variables. In the medium and long term. and for the results of the Difference Test there is a significant difference during and before covid 19 by the country of Heaven Earth. Suggestions in this study, To stabilize the Inflation and Unemployment rates, government policies are needed to increase interest rates which have an impact on reducing the inflation rate from this decrease in the inflation rate also has an impact on unemployment where when inflation falls, many industrial sectors need more workers to get maximum production results which of course will reduce the Unemployment rate.